A new species of the pseudoscorpion genus Megachernes (Pseudoscorpiones: Chernetidae) associated with a threatened Sri Lankan rainforest rodent, with a review of host associations of Megachernes - Harvey, Mark S.; Ratnaweera, Pamoda B.; Udagama, Preethi V.; Wijesinghe, Mayuri R. (Journal of Natural History, 2012)
Most species of the Old World pseudoscorpion genus Megachernes are associated with mammals, either within their nests or in their pelage, whereas others are found in cave systems, usually in bat guano. The ﬁrst Sri Lankan species of the genus, Megachernes kanneliyensis, is described from the fur of an endemic, threatened Sri Lankan mouse, Mus mayori pococki from the Kanneliya rainforest. The species is compared with other species of the genus. Host associations of all named and several unnamed species of Megachernes are reviewed, with two main habitat types, those found in mammal nests and in their pelage, and those found in bat guano. Based on similarities with Megachernes, Chiridiochernes is transferred to Lamprochernetinae as the spermathecae are T-shaped, the sole diagnostic feature of the subfamily.
Keywords: threatened species; rainforest; Mus mayori pococki; morphology; taxonomy